Positive plate and application thereof

By using gradient lithium iron phosphate and ternary urban material structures distributed in the positive active layer of the lithium ion battery positive film, it solves the problem of lithium analysis of the battery under the energy density and safety performance, which significantly improves the cycle performance of the battery and the cycle performance of the battery and the cycle performance of the battery and the cycle performance of the battery and the cycle performance and Safety performance.

CN119381400AActive Publication Date: 2025-01-28ZHUHAI COSMX BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411544437.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

On the basis of ensuring high energy density and safety performance, existing lithium-ion batteries are difficult to effectively improve the lithium-ion problem, affecting the cycling performance of the battery.

Method used

Design a kind of positive film, its positive active layer is not less than 3 layers, lithium iron phosphate and ternary positive electrode materials are distributed in the thickness direction, and the content of the three yuan positive materials near the surface of the positive polarization fluid surface gradually decreases, away from side phosphate iron phosphate The lithium content gradually increases.

Benefits of technology

Through the urban active material structure of the gradient distribution, the cycle performance and safety performance of the lithium ion battery are improved, and the lithium analysis is effectively avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381400A_ABST
    Figure CN119381400A_ABST
Patent Text Reader

Abstract

The invention provides a positive plate and application thereof, the positive plate comprises a positive current collector and n positive active layers arranged on at least part of the surface of the positive current collector, and n is an integer greater than or equal to 3; the n positive electrode active layers are sequentially stacked on the surface perpendicular to the positive electrode current collector, each positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises lithium iron phosphate and a ternary positive electrode material; in the thickness direction of the positive electrode active layer, from one side close to the surface of the positive electrode current collector to one side far away from the surface of the positive electrode current collector, the mass content of the ternary positive electrode material in each positive electrode active layer is gradually reduced, and the mass content of the lithium iron phosphate is gradually increased. Due to the special structure, the lithium ion battery has relatively high cycle performance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries and relates to a positive electrode sheet, and in particular to a positive electrode sheet and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices (such as laptops, tablets, smart phones, etc.), electric vehicles, marine maritime, aerospace and other technical fields due to their advantages such as high voltage platform, long service life, low self-discharge rate, no memory effect, and green environmental protection. However, with the rapid development of commercial society, the energy density and safety performance of batteries cannot meet the demand.

[0003] As one of the key components of lithium-ion batteries, positive electrode active materials play a vital role in improving battery performance. At present, the mainstream positive electrode active materials are mainly lithium iron phosphate and ternary positive electrode materials. Among them, lithium iron phosphate has the advantages of high safety, long service life and low cost, but its battery consistency is poor, energy density is low, and low-temperature performance needs to be improved; while ternary positive electrode materials have higher energy density than lithium iron phosphate and better rate performance, but they are more expensive, have poor safety performance, and have the risk of fire and spontaneous combustion during cyclic use.

[0004] At present, the common method is to directly mix lithium iron phosphate and ternary positive electrode materials to make the battery have both high energy density and safety performance. However, it is difficult for this method to fully bring out the advantages of both. In addition, direct mixing can easily lead to lithium deposition on the surface of the negative electrode, affecting the battery's cycle performance.

[0005] Therefore, how to improve the lithium plating problem and effectively improve the battery's cycle performance while ensuring high energy density and safety performance is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the above-mentioned defects, the present invention provides a positive electrode sheet, in which the positive electrode active layer is not less than 3 layers, and in the thickness direction, from the side close to the positive electrode current collector surface to the side far from the positive electrode current collector surface, the mass content of lithium iron phosphate gradually increases, and the mass content of the ternary positive electrode material gradually decreases. This special structure can make the lithium-ion battery have both higher cycle performance and safety performance.

[0007] The present invention also provides a lithium ion battery, which comprises the positive electrode sheet, so the lithium ion battery has higher cycle performance and safety performance.

[0008] The present invention provides a positive electrode sheet, comprising a positive electrode current collector and n positive electrode active layers arranged on at least a portion of the surface of the positive electrode current collector, where n is an integer greater than or equal to 3;

[0009] The n positive electrode active layers are stacked in sequence on a surface perpendicular to the positive electrode current collector, each positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises lithium iron phosphate and a ternary positive electrode material;

[0010] In the thickness direction of the positive electrode active layer, from the side close to the positive electrode collector surface to the side away from the positive electrode collector surface, the mass content of the ternary positive electrode material in each layer of the positive electrode active layer gradually decreases, and the mass content of lithium iron phosphate in each layer of the positive electrode active layer gradually increases.

[0011] Furthermore, in the positive electrode active material of the first positive electrode active layer, the mass content of the ternary positive electrode material is not less than 99%;

[0012] And / or, in the positive electrode active material of the n-th positive electrode active layer, the mass content of the lithium iron phosphate is not less than 99%.

[0013] Further, the thickness of the first positive electrode active layer is equal to the thickness of the nth positive electrode active layer;

[0014] Preferably, the total thickness H of the n-layer positive electrode active layer on one side is ≤400 μm.

[0015] Furthermore, a recessed portion is provided on the outer surface of the positive electrode active layer;

[0016] Preferably, the depth d of the recessed portion is equal to the single-side thickness h of the nth positive electrode active layer. n Satisfied: 0.01h n ≤d≤h n ;

[0017] More preferably, the depth d of the recessed portion is 1 to 20 μm.

[0018] Furthermore, the maximum size s of the recessed portions is 5 to 200 μm, and / or the interval t of the recessed portions is 100 to 2000 μm.

[0019] Furthermore, the median particle size Dv50 of the ternary positive electrode material is 5 to 15 μm, and / or the median particle size Dv50 of the lithium iron phosphate is 1 to 2.5 μm.

[0020] The present invention also provides a lithium-ion battery, comprising any one of the above-mentioned positive electrode sheets.

[0021] Furthermore, the lithium-ion battery also includes an electrolyte, and the electrolyte includes a nitrile additive and an ether nitrile additive;

[0022] The nitrile additive includes at least one of succinonitrile, 1,3,6-hexanetricarbonitrile, 1,3,5-pentanetricarbonitrile, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, tricyanobenzene, acrylonitrile, and 1,2,3-tris(cyanoethoxy)propane;

[0023] The ether nitrile additive includes at least one of 1,2,3-tri(cyanoethoxy)propane, ethylene glycol di(2-cyanoethyl) ether, and diethylene glycol di(2-cyanoethyl) ether.

[0024] Furthermore, the sum of the mass percentage content i of the nitrile additive and the mass percentage content j of the ether nitrile additive in the electrolyte is 2 to 18%;

[0025] Preferably, 2i≤j;

[0026] More preferably, i is 0.1 to 10%, and / or j is 0.1 to 8%.

[0027] Furthermore, the lithium-ion battery meets the following requirements: 0.5h n / H≤i≤5h n / H+8,0.5h n / H≤j≤5h n / H+8.

[0028] The positive electrode sheet in the present invention includes no less than 3 layers of positive electrode active layers, and each positive electrode active layer includes positive electrode active materials lithium iron phosphate and ternary positive electrode materials. By making the lithium iron phosphate and ternary positive electrode materials present a gradient distribution, that is, in the thickness direction of the positive electrode active layer, from the side close to the positive electrode current collector to the side away from the positive electrode current collector, the lithium iron phosphate content gradually increases, and the ternary positive electrode material content gradually decreases, the uniformity of lithium iron phosphate and ternary positive electrode materials per unit area is effectively improved, and the black spots or lithium precipitation problems on the negative electrode surface are improved. Therefore, the positive electrode sheet of this special structure in the present invention can effectively improve the safety performance and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet of the present invention;

[0030] Figure 2 A schematic diagram of a positive electrode sheet including a positive electrode tab of the present invention;

[0031] Figure 3 This is a SEM image of the depressed portion on the surface of the positive electrode active layer in Example 1 of the present invention.

[0032] Description of reference numerals:

[0033] 1- positive electrode current collector;

[0034] 2-1st positive electrode active layer;

[0035] 3- The second positive electrode active layer;

[0036] 4-nth positive electrode active layer;

[0037] 5- positive electrode tab;

[0038] 6- positive electrode ear tape;

[0039] 7- Negative electrode tab tape 7. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] A first aspect of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and n positive electrode active layers disposed on at least a portion of the surface of the positive electrode current collector, where n is an integer greater than or equal to 3;

[0042] n positive electrode active layers are stacked in sequence on a surface perpendicular to the positive electrode current collector, each positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises lithium iron phosphate and a ternary positive electrode material;

[0043] In the thickness direction of the positive electrode active layer, from the side close to the positive electrode collector surface to the side far from the positive electrode collector surface, the mass content of the ternary positive electrode material in each positive electrode active layer gradually decreases, and the mass content of lithium iron phosphate in each positive electrode active layer gradually increases.

[0044] Figure 1 It is a schematic diagram of the structure of the positive electrode. Figure 1 In the figure, the Z direction is the thickness direction of the positive electrode active layer, the positive electrode active layer is arranged on one side of the positive electrode collector 1, and the first positive electrode active layer 2, the second positive electrode active layer 3, ..., the nth positive electrode active layer 4 are stacked in sequence on the surface perpendicular to the positive electrode collector 1; and in the thickness direction of the positive electrode active layer, from the side close to the surface of the positive electrode collector to the side far from the surface of the positive electrode collector, the mass content of lithium iron phosphate in each positive electrode active layer gradually increases, and the mass content of the ternary positive electrode material gradually decreases.

[0045] After research, the inventors found that, in order to achieve high energy density and high safety performance, ternary positive electrode materials and lithium iron phosphate are often directly blended and coated. However, the capacity of the ternary positive electrode material is higher than that of lithium iron phosphate. Therefore, under high voltage, the decay of the ternary positive electrode material is faster than that of the lithium iron phosphate material. Due to the difference in particle size between the ternary positive electrode material and the lithium iron phosphate, it is difficult to achieve complete uniformity of the ternary positive electrode material and the lithium iron phosphate material. In this case, in the area where the ternary positive electrode material is enriched, since the capacity of the ternary positive electrode material is higher, more lithium ions need to be absorbed in the initial stage of the cycle, but the negative electrode is uniform as a whole, and the concentration difference caused by the transmission of lithium ions to the ternary positive electrode material becomes larger and larger, thereby aggravating the uneven lithium insertion of the negative electrode sheet; in the later stage of the cycle, the decay of the ternary positive electrode material is accelerated, resulting in the poor ability of the area where the ternary positive electrode material is enriched to absorb lithium ions, and the corresponding negative electrode area can receive fewer lithium ions, so the area where the ternary positive electrode material is enriched is prone to black spots or lithium precipitation.

[0046] In the present invention, by arranging no less than 3 layers of positive electrode active layers on at least part of the surface of the positive electrode current collector, and each layer of the positive electrode active layer includes lithium iron phosphate and a ternary positive electrode material, the distribution uniformity of the lithium iron phosphate and the ternary positive electrode material in the thickness direction can be effectively improved, the difference in slurry viscosity and surface tension between different numbers of layers can be reduced, the transmission or diffusion impedance of lithium ions between layers can be reduced, and the cycle performance and fast charging performance of the battery can be effectively improved.

[0047] At the same time, in the thickness direction of the positive electrode active layer, from the side close to the positive electrode current collector to the side away from the positive electrode current collector, the content of lithium iron phosphate gradually increases, and the content of ternary positive electrode material gradually decreases. This gradient distribution structure helps to improve the uniformity of lithium iron phosphate and ternary positive electrode materials per unit area, thereby effectively avoiding black spots or lithium precipitation caused by uneven distribution. Moreover, since the ternary positive electrode material is alkaline, it is easy to absorb water and carbon dioxide in the air, and more side reactions are prone to occur in the later stage of the cycle, affecting the safety performance of the battery; and this special structure can reduce the negative impact of alkalinity, reduce the side reactions between the positive electrode side and the electrolyte to a certain extent, and improve the cycle stability. In addition, by controlling the highest content of ternary positive electrode material in the surface close to the positive electrode current collector, a higher energy density can be guaranteed; and the highest content of lithium iron phosphate in the surface away from the positive electrode current collector makes the temperature transfer from the outside of the electrode to the inside, after the inner ternary positive electrode material reaches the failure temperature, the outermost lithium iron phosphate material has not yet failed, thereby delaying the increase in the internal temperature of the battery caused by the failure of the ternary positive electrode material, and improving the safety performance of the battery.

[0048] In summary, the positive electrode sheet in the present invention can effectively improve the cycle performance and safety performance of the battery.

[0049] The positive electrode current collector in the present invention can be a material commonly used by those skilled in the art, such as aluminum foil.

[0050] The present invention does not specifically limit the sources of lithium iron phosphate and ternary positive electrode materials, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.

[0051] In a specific embodiment, the mass content of the ternary positive electrode material in the positive electrode active material of the first positive electrode active layer is not less than 99%. In this case, the energy density of the battery can be further improved while ensuring the safety performance.

[0052] In a specific embodiment, the mass content of lithium iron phosphate in the positive electrode active material of the nth positive electrode active layer is not less than 99%. In this case, the battery can not only have a higher energy density, but also further improve the safety performance of the battery.

[0053] In a specific embodiment, the n-layer positive electrode active layer satisfies: y=p*ln(m)+q, wherein p and q are constants, and y is the mass percentage of the ternary positive electrode material in the positive electrode active material in the m-th positive electrode active layer.

[0054] When the n-layer positive electrode active layer satisfies the above relationship, the distribution uniformity of lithium iron phosphate and ternary positive electrode materials in the thickness direction can be further improved, which helps to narrow the differences in slurry viscosity and surface tension between different numbers of layers, reduce the transmission or diffusion impedance of lithium ions between layers, and further improve the battery's cycle performance and fast charging performance.

[0055] It should be noted that the above constants p and q can be calculated by substituting the mass content of the ternary positive electrode material in the first positive electrode active layer and the mass content of the ternary positive electrode material in the nth positive electrode active layer into the relationship y=p*ln(m)+q. Furthermore, the mass content of the ternary positive electrode material in the mth positive electrode active layer can be obtained by substituting m into the above relationship.

[0056] For example, when n is 10, the mass content of the ternary positive electrode material in the first positive electrode active layer is 100%, and the mass content of the ternary positive electrode material in the tenth positive electrode active layer is 0. Substituting y=p*ln(m)+q, p=-0.434, q=1, the relationship is y=-0.434*ln(m)+1, then the mass content of the ternary positive electrode material in the second layer in the positive electrode active material is -0.4 34*ln(2)+1=0.6992, which is 69.92%; the mass content of the ternary positive electrode material in the positive electrode active material in the third layer is -0.434*ln(3)+1=0.5232, which is 52.32%; and so on, ...; the mass content of the ternary positive electrode material in the positive electrode active material in the ninth layer is -0.434*ln(9)+1=0.0464, which is 4.64%.

[0057] In a specific embodiment, the thickness of the first positive electrode active layer is equal to the thickness of the nth positive electrode active layer;

[0058] The n-layer positive electrode active layer satisfies: h m =am 2 +bm+c, where h (n+1) / 2 =0, a, b, c are constants, h m is the thickness of the mth positive electrode active layer;

[0059] Preferably, the total thickness H of the n-layer positive electrode active layer on one side is ≤400 μm.

[0060] When the positive electrode active layer satisfies the above relationship, the thickness of the first and nth positive electrode active layers can be made moderate, which can not only ensure higher thermal stability, but also further improve the energy density of the battery, thereby further improving the overall energy density and safety performance of the battery cell.

[0061] Furthermore, when the total thickness of the single side of the n-layer positive electrode active layer is H≤400 μm, the lithium ion transport channel is shorter and the wettability of the electrolyte is better, which is beneficial to the transmission of lithium ions and reduces the risk of polarization and lithium precipitation.

[0062] Exemplarily, H is 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm or 400 μm.

[0063] It can be understood that the total thickness of the n-layer positive electrode active layer on one side of the positive electrode current collector in the present invention refers to the total thickness of the n-layer positive electrode active layer on one side after rolling.

[0064] It should be noted that the above constants a, b, and c can be obtained by substituting the thickness of the first positive electrode active layer, the thickness of the nth positive electrode active layer, and h (n+1) / 2 =0 Substitute into the relation h m =am 2Furthermore, the thickness of the m-th positive electrode active layer can be obtained by simply substituting m into the above relationship.

[0065] For example, when n is 10, the thickness of the first positive electrode active layer is 30 μm, the thickness of the tenth positive electrode active layer is 30 μm, and h (10+1) / 2 = 0, substitute h m =am 2 +bm+c, we get a=1.4815, b=-16.296, c=44.815, so the relationship is h m =1.4815m 2 -16.296m+44.815, then the thickness of the second positive electrode active layer is 1.4815*2 2 -16.296*2+44.815=18.15, which is 18.15 μm. The thickness of the third positive electrode active layer is 1.4815*3 2 -16.296*3+44.815=9.26, which is 9.26 μm, ..., the thickness of the 9th positive electrode active layer is 1.4815*9 2 -16.296*9+44.815=18.15, which is 18.15 μm.

[0066] In a specific embodiment, a recessed portion is provided on the outer surface of the positive electrode active layer;

[0067] Preferably, the depth d of the recessed portion is equal to the single-side thickness h of the nth positive electrode active layer. n Satisfied: 0.01h n ≤d≤h n ;

[0068] More preferably, the depth d of the depressed portion is 1 to 20 μm.

[0069] By providing a recessed portion on the outer surface of the positive electrode active layer, on the one hand, the wettability and liquid retention capacity of the electrolyte to the electrode sheet can be effectively improved, thereby avoiding poor electrolyte infiltration and insufficient electrolyte during long cycles that affect the transmission of lithium ions, and further improving the cycle performance of the battery; on the other hand, a certain space can be reserved for the volume expansion of the negative electrode active material, thereby improving the problem of decreased cycle performance caused by volume expansion.

[0070] Furthermore, when the depth d of the recessed portion is equal to the thickness h of the nth positive electrode active layer n Meet 0.01h n ≤d≤h nWhen the positive electrode sheet has a high liquid retention capacity and the battery's rate performance and cycle performance are improved, the n-th positive electrode active layer will not affect the protection of the inner active material, and will not hinder the temperature from being transferred from the outside to the inside of the electrode, thereby making the battery have a higher safety performance.

[0071] Furthermore, the depth d of the concave portion is 1 to 20 μm. Within this range, the battery can have higher cycle performance, rate performance and safety performance.

[0072] Illustratively, d is 1 μm, 5 μm, 10 μm, 15 μm or 20 μm.

[0073] It should be noted that the recessed portion is arranged in an area other than the adhesive tape position. Figure 2 Schematic diagram of a positive electrode sheet including a positive electrode tab, Figure 2 In the figure, the positive electrode tab 5 is arranged on the surface of the positive electrode current collector 1 (the positive electrode active layer is not arranged in the area where the positive electrode tab is arranged), there is a positive electrode tab tape 6 on the surface of the positive electrode tab 5, and there is a negative electrode tab tape 7 at the position corresponding to the negative electrode tab, which plays a role in preventing burrs from piercing the diaphragm and causing short circuit.

[0074] The present invention does not specifically limit the shape of the recessed portion, for example, it may be at least one of a circular shape, an elliptical shape, and a polygonal shape.

[0075] The present invention does not specifically limit the implementation method of the recessed portion. For example, an embossing roller may be used to form an uneven pattern, namely the recessed portion, on the surface of the pole piece.

[0076] In a specific embodiment, the maximum size s of the concave portion is 5 to 200 μm. Within this range, the battery can accommodate more free electrolyte, and the overall wettability of the battery cell is better, which is conducive to the long cycle and high safety of the battery cell; at the same time, the "wave sheet" phenomenon will not appear during winding, reducing the risk of lithium deposition and even fire in the later stage of the cycle.

[0077] The maximum size s of the recessed portion in the present invention refers to a circumscribed circle of the outer contour of the recessed portion, and the diameter of the circumscribed circle is the maximum size s of the recessed portion.

[0078] Exemplarily, s is 5 μm, 50 μm, 100 μm, 150 μm or 200 μm.

[0079] In a specific embodiment, the spacing t of the recessed portions is 100 to 2000 μm. Within this range, the integrity of the electrode can be improved while ensuring the wettability of the electrolyte to the electrode and the electrode's ability to retain liquid, so that the surface roughness of the electrode is moderate, avoiding poor formation due to excessive roughness and the problem of lithium deposition at the tip.

[0080] The pitch of the recessed portions in the present invention refers to the distance between the centers of two adjacent recessed portions.

[0081] Exemplarily, t is 100 μm, 500 μm, 1000 μm, 1500 μm or 2000 μm.

[0082] It is understandable that although the battery cycle performance can be improved by setting a concave portion on the surface of the positive electrode active layer, the concave portion will form a convex point, that is, the junction of the concave portion and the flat portion, causing the sharp convex point and lithium precipitation problem. In order to improve this problem, the pressure can be reduced in the formation treatment of the battery, specifically, compared with the theoretical formation pressure, it is reduced by d / 2.5H MPa.

[0083] In a specific embodiment, the median particle size Dv50 of the ternary cathode material is 5 to 15 μm, and / or the median particle size Dv50 of the lithium iron phosphate is 1 to 2.5 μm. Within this range, on the one hand, the consumption of the electrolyte can be reduced, and the black spot problem caused by the drying of the electrolyte in the late cycle can be alleviated; on the other hand, it is conducive to the smooth transmission of lithium ions and reduces the transmission impedance, thereby further improving the cycle performance and safety performance of the battery.

[0084] The "median particle size Dv50" in the present invention refers to the particle size corresponding to when the cumulative volume distribution of the ternary positive electrode material particles or lithium iron phosphate particles reaches 50%, which can be obtained by testing with a laser particle size analyzer.

[0085] Exemplarily, the median particle size Dv50 of the ternary positive electrode material is 5μm, 7μm, 9μm, 11μm, 13μm or 15μm; and / or the median particle size Dv50 of lithium iron phosphate is 1μm, 1.3μm, 1.6μm, 1.9μm, 2.2μm or 2.5μm.

[0086] The second aspect of the present invention provides a lithium ion battery, comprising the positive electrode sheet of the first aspect. Therefore, the lithium ion battery has higher cycle performance and safety performance.

[0087] The lithium ion battery in the present invention can be a wound type battery or a stacked type battery.

[0088] The present invention does not specifically limit the method for preparing the lithium-ion battery, and the lithium-ion battery can be prepared by common methods used by those skilled in the art.

[0089] In a specific embodiment, the lithium ion battery further comprises an electrolyte, and the electrolyte comprises a nitrile additive and an ether nitrile additive;

[0090] The nitrile additive includes at least one of succinonitrile, 1,3,6-hexanetricarbonitrile, 1,3,5-pentanetricarbonitrile, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, tricyanobenzene, acrylonitrile, and 1,2,3-tris(cyanoethoxy)propane;

[0091] The ether nitrile additive includes at least one of 1,2,3-tri(cyanoethoxy)propane, ethylene glycol di(2-cyanoethyl) ether, and diethylene glycol di(2-cyanoethyl) ether.

[0092] When the electrolyte includes nitrile additives and ether nitrile additives, the two work together, and the nitrile additives can coordinate with the cobalt ions in the positive electrode to form a complex, which can inhibit the dissolution of cobalt ions to a certain extent and maintain the stability of the positive electrode; however, there are still exposed active sites in the positive electrode, and the CO bonds contained in the ether nitrile additives can undergo oxidation reactions during the discharge process, participate in the formation of the interface film, and the cyanide product generated after oxidation can also continue to react with the cobalt ions to form a stable and firm interface film, further inhibiting the dissolution of transition metal ions in the positive electrode and improving the cycle performance of the battery; at the same time, although the concave part on the surface of the positive electrode active layer can improve the wettability of the electrolyte and improve the volume expansion of the negative electrode, convex points will be formed in the concave part (i.e., the junction of the concave part and the flat part), which is prone to lithium precipitation problems. Nitrile additives and ether nitrile additives, especially ether nitrile additives, can preferentially form films at the convex points, reduce the surface roughness of the pole piece, thereby reducing impedance, reducing the risk of lithium precipitation and capacity diving, and effectively improving the safety performance of the battery. Therefore, when the electrolyte includes both nitrile additives and ether nitrile additives, the cycle performance and safety performance of the battery can be further improved.

[0093] When the nitrile additive and the ether nitrile additive are respectively a mixture of the aforementioned specific compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0094] The present invention does not specifically limit the sources of the nitrile additives and the ether nitrile additives, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.

[0095] In a specific embodiment, the sum of the mass percentage content i of the nitrile additive and the mass percentage content j of the ether nitrile additive in the electrolyte is 2 to 18%;

[0096] Preferably, 2i≤j;

[0097] More preferably, i is 0.1 to 10%, and / or j is 0.1 to 8%.

[0098] When the sum of the mass contents of nitrile compounds and ether nitrile compounds in the electrolyte is within the aforementioned range, further satisfying 2i≤j, and further satisfying i is 0.1-10%, and / or j is 0.1-8%, the two can work better together to further improve the cycle performance and safety performance of the battery.

[0099] Illustratively, the sum of i and j is 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16% or 18%.

[0100] Illustratively, i is 0.1%, 1%, 2%, 4%, 6%, 8% or 10%; j is 0.1%, 1%, 3%, 4%, 5%, 6%, 7% or 8%.

[0101] It can be understood that the electrolyte also includes lithium salt and organic solvent; wherein the lithium salt is preferably at least one of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorophosphate (LiPF6); the organic solvent is preferably at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and methyl propyl carbonate (MPC).

[0102] In a specific embodiment, the lithium-ion battery meets the following requirements: 0.5h n / H≤i≤5h n / H+8,0.5h n / H≤j≤5h n / H+8. When the lithium-ion battery meets the above relationship, not only can a sufficient protective film be formed on the bumps to ensure the safety of the battery cell, but also the excessive impedance of the electrolyte caused by excessive ether nitrile additives can be avoided, thereby further reducing the risk of lithium plating and capacity drop.

[0103] It can be understood that the lithium-ion battery also includes a negative electrode sheet, which includes a negative electrode collector and a negative electrode active layer disposed on at least a portion of the surface of the negative electrode collector; the negative electrode active layer includes a negative electrode active material.

[0104] The negative electrode current collector in the present invention can be a material commonly used by those skilled in the art, such as copper foil.

[0105] The negative electrode active material in the present invention is preferably at least one of artificial graphite, natural graphite, tin-based negative electrode material, lithium-containing transition metal nitride negative electrode material, alloy negative electrode material, and nanoscale negative electrode material.

[0106] Hereinafter, a lithium-ion battery including the positive electrode sheet of the present invention will be described in detail through specific embodiments.

[0107] Example 1

[0108] 1) In this embodiment, there are 4 positive electrode active layers, the mass content of the ternary positive electrode material NCM613 (Dv50 is 10 μm) in the first positive electrode active layer is 100%, and the mass content of the ternary positive electrode material NCM613 in the fourth positive electrode active layer is 0. Substituting into y=p*ln(m)+q, it is calculated that p=-0.721, q=1, then y=-0.721*ln(m)+1, then the mass content of the ternary positive electrode material in the second positive electrode active layer is 50%, and the mass content of the ternary positive electrode material in the third positive electrode active layer is 20.8%;

[0109] The thickness of the first positive electrode active layer and the fourth positive electrode active layer are both set to 100 μm. (4+1) / 2 = 0, substitute h = am 2 +bm+c, we get a=44.444, b=-222.22, c=277.78, so the relationship is h=44.444m 2 -222.22m+277.78, then the thickness of the second positive electrode active layer is 11.12μm, and the thickness of the third positive electrode active layer is 11.12μm;

[0110] The ternary positive electrode material NCM613 (Dv50 is 10 μm), lithium iron phosphate LiFePO4 (Dv50 is 1.5 μm), conductive agent carbon black, and binder PVDF are mixed in a mass ratio of 96.5:0:2:1.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to obtain the first positive electrode active layer slurry;

[0111] The ternary positive electrode material NCM613 (Dv50 is 10 μm), lithium iron phosphate LiFePO4 (Dv50 is 1.5 μm), conductive agent carbon black, and binder PVDF are mixed in a mass ratio of 48.27:48.23:2:1.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to obtain the second positive electrode active layer slurry;

[0112] The ternary positive electrode material NCM613 (Dv50 is 10 μm), lithium iron phosphate LiFePO4 (Dv50 is 1.5 μm), conductive agent carbon black, and binder PVDF are mixed in a mass ratio of 20.06:76.44:2:1.5, N-methylpyrrolidone (NMP) is added, and the third positive electrode active layer slurry is obtained after stirring evenly;

[0113] The ternary positive electrode material NCM613 (Dv50 is 10 μm), lithium iron phosphate LiFePO4 (Dv50 is 1.5 μm), conductive agent carbon black, and binder PVDF are mixed in a mass ratio of 0:96.5:2:1.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly to obtain the fourth positive electrode active layer slurry;

[0114] The first positive electrode active layer slurry, the second positive electrode active layer slurry, the third positive electrode active layer slurry and the fourth positive electrode active layer slurry are sequentially coated on the surface of the positive electrode current collector aluminum foil, and the positive electrode sheets are obtained after drying, rolling and slitting, wherein the first positive electrode active layer has a thickness of 100 μm, the second positive electrode active layer has a thickness of 11.12 μm, the third positive electrode active layer has a thickness of 11.12 μm, and the fourth positive electrode active layer has a thickness of 100 μm;

[0115] Finally, an embossing roller was used to perform embossing treatment to form depressions on the surface of the positive electrode active layer. The depressions had a spacing of 500 μm, a depth of 5 μm, and a maximum size of 50 μm. Figure 3 This is a SEM image of the concave portion on the surface of the positive electrode active layer in Example 1;

[0116] 2) adding artificial graphite, a negative electrode active material, carbon fiber, a conductive agent, and styrene-butadiene rubber (SBR), a binder, into a stirring tank in a mass ratio of 98.2:0.6:1.2, adding deionized water, stirring thoroughly, and passing through a 150-mesh sieve to prepare a negative electrode slurry; coating the negative electrode slurry onto a copper foil surface using a coating machine, drying (100° C.), rolling, and slitting to obtain a negative electrode sheet;

[0117] 3) In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC), propylene carbonate (PC) and other solvents (ethyl propionate (EP), ethyl butyrate (EB), ethyl acetate (EA) and other volume ratios) were mixed in a volume ratio of 20:20:60; then 15wt% of fully dried lithium salt lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte was quickly added thereto, and the solution was stirred for 2 hours. After the electrolyte is dissolved, 2.0 wt% of a nitrile additive (including succinonitrile, tricyanobenzene, acrylonitrile and 1,2,3-tri(cyanoethoxy)propane in a mass ratio of 1:1:1:1) is added based on the total mass of the electrolyte, and then 4 wt% of an ether nitrile additive (including 1,2,3-tri(cyanoethoxy)propane and ethylene glycol di(2-cyanoethyl)ether in a mass ratio of 1:1) is added based on the total mass of the electrolyte, and after stirring evenly, the electrolyte is obtained after the water content and free acid are tested to be qualified;

[0118] 4) The positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, wound to form a battery cell, and then packaged with aluminum-plastic film, baked to remove moisture, and then injected with electrolyte, and then subjected to formation (theoretical formation pressure is 1.1 MPa, actual formation pressure is 1.09 MPa), secondary sealing, etc., to obtain a lithium-ion battery.

[0119] Example 2

[0120] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the Dv50 of the ternary positive electrode material NCM613 is adjusted to 5 μm, the Dv50 of the lithium iron phosphate LiFePO4 is adjusted to 1 μm, and the others remain unchanged.

[0121] Example 3

[0122] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the Dv50 of the ternary positive electrode material NCM613 is adjusted to 15 μm, the Dv50 of the lithium iron phosphate LiFePO4 is adjusted to 2.5 μm, and the others remain unchanged.

[0123] Example 4

[0124] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the spacing of the recessed portions is adjusted to 100 μm, the depth is adjusted to 1 μm, and the maximum size is adjusted to 5 μm.

[0125] Example 5

[0126] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the spacing of the recessed portions is adjusted to 2000 μm, the depth is adjusted to 20 μm, and the maximum size is adjusted to 200 μm.

[0127] Example 6

[0128] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage of the nitrile additive in the electrolyte is adjusted to 4%, and the mass percentage of the ether nitrile additive in the electrolyte is adjusted to 8%.

[0129] Example 7

[0130] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage of the nitrile additive in the electrolyte is adjusted to 1%, and the mass percentage of the ether nitrile additive in the electrolyte is adjusted to 2%.

[0131] Example 8

[0132] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage of the nitrile additive in the electrolyte is adjusted to 2%, and the mass percentage of the ether nitrile additive in the electrolyte is adjusted to 6%.

[0133] Example 9

[0134] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that, in step 1), there are 7 positive electrode active layers, the mass content of the ternary positive electrode material NCM613 in the first positive electrode active layer is 100%, and the mass content of the ternary positive electrode material NCM613 in the seventh positive electrode active layer is 0. Substituting into y=p*ln(m)+q, it is calculated that p=-0.514, q=1, then y=-0.514*ln(m)+1, then the mass contents of the ternary positive electrode material in the positive electrode active material in the second, third, fourth, fifth and sixth positive electrode active layers are 64.37%, 43.53%, 28.74%, 17.27% and 7.90%, respectively;

[0135] The thickness of the first positive electrode active layer and the seventh positive electrode active layer are both set to 100 μm. (7+1) / 2 = 0, substitute h = am 2 +bm+c, we get a=11.111, b=-88.889, c=177.78, so the relationship is h=11.111m 2 -88.889m+177.78, then the thicknesses of the second, third, fourth, fifth and sixth positive electrode active layers are 44.45μm, 11.11μm, 0, 11.11μm and 44.44μm respectively;

[0136] Then the mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the second positive electrode active layer slurry is 62.12:34.38:2:1.5;

[0137] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the third positive electrode active layer slurry is 42.01:54.49:2:1.5;

[0138] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the fifth positive electrode active layer is 42.01:54.49:2:1.5;

[0139] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the sixth positive electrode active layer is 7.63:88.87:2:1.5.

[0140] Example 10

[0141] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), there are 10 positive electrode active layers, the mass content of the ternary positive electrode material NCM613 in the first positive electrode active layer is 100%, and the mass content of the ternary positive electrode material NCM613 in the tenth positive electrode active layer is 0. Substituting into y=p*ln(m)+q, it is calculated that: p=-0.434,q=1,then y=-0.434*ln(m)+1,then the mass contents of the ternary positive electrode material in the positive electrode active material in the second, third, fourth, fifth, sixth, seventh, eighth and ninth positive electrode active layers are 69.92%, 52.32%, 39.83%, 30.15%, 22.24%, 15.55%, 9.75% and 4.64% respectively;

[0142] The thickness of the first positive electrode active layer and the tenth positive electrode active layer are both set to 100 μm. (10+1) / 2 = 0, substitute h = am 2 +bm+c, we get a=1.4815, b=-16.296, c=44.815, so the relationship is h=1.4815m 2 -16.296m+44.815, then the thicknesses of the second, third, fourth, fifth, sixth, seventh, eighth and ninth positive electrode active layers are 18.15μm, 9.26μm, 3.34μm, 0.37μm, 0.37μm, 3.34μm, 9.26μm and 18.15μm respectively;

[0143] Then the mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the second positive electrode active layer slurry is 67.47:29.03:2:1.5;

[0144] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the third positive electrode active layer slurry is 50.49:46.01:2:1.5;

[0145] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the fourth positive electrode active layer slurry is 38.44:58.06:2:1.5;

[0146] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the fifth positive electrode active layer is 29.10:67.40:2:1.5;

[0147] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the sixth positive electrode active layer is 21.46:75.04:2:1.5

[0148] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the 7th positive electrode active layer is 15.00:81.50:2:1.5

[0149] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the 8th positive electrode active layer slurry is 9.41:87.09:2:1.5

[0150] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the 9th positive electrode active layer is 4.48:92.02:2:1.5.

[0151] Embodiment 11

[0152] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass content of the ternary positive electrode material in the second positive electrode active layer is adjusted to 67% in the positive electrode active material, and the mass content of the ternary positive electrode material in the third positive electrode active layer is adjusted to 34% in the positive electrode active material;

[0153] Then the mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the second positive electrode active layer slurry is 64.65:31.85:2:1.5;

[0154] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the third positive electrode active layer slurry is 32.81:63.69:2:1.5.

[0155] Example 12

[0156] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the thickness of the second positive electrode active layer is adjusted to 60 μm, the thickness of the third positive electrode active layer is adjusted to 40 μm, and the thickness of the fourth positive electrode active layer is adjusted to 22 μm.

[0157] Embodiment 13

[0158] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), the thickness of the first positive electrode active layer and the fourth positive electrode active layer are both set to 200 μm, then a=88.889, b=-444.44, c=555.56, and the relationship is h=88.889m 2 -444.44m+555.56, then the thickness of the second positive electrode active layer is 22.24μm, and the thickness of the third positive electrode active layer is 22.24μm.

[0159] Embodiment 14

[0160] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the positive electrode sheet is not embossed, and there is no concave portion on the surface of the positive electrode active layer.

[0161] Embodiment 15

[0162] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the depth of the recessed portion is adjusted to 0.5 μm.

[0163] Example 16

[0164] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the depth of the recessed portion is adjusted to 25 μm.

[0165] Embodiment 17

[0166] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the maximum size of the recessed portion is adjusted to 400 μm.

[0167] Embodiment 18

[0168] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the spacing between the recessed portions is adjusted to 10 μm.

[0169] Embodiment 19

[0170] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the Dv50 of the ternary positive electrode material NCM613 is adjusted to 3.5 μm, and the Dv50 of the lithium iron phosphate LiFePO4 is adjusted to 0.8 μm, while the others remain unchanged.

[0171] Embodiment 20

[0172] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the electrolyte does not include nitrile additives and ether nitrile additives, and accordingly, the mass percentage of the organic solvent in the electrolyte becomes 85%.

[0173] Embodiment 21

[0174] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the electrolyte does not include nitrile additives, and accordingly, the mass percentage of the organic solvent in the electrolyte becomes 82.8%.

[0175] Embodiment 22

[0176] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the electrolyte does not include ether nitrile additives, and accordingly, the mass percentage of the organic solvent in the electrolyte becomes 83%.

[0177] Embodiment 23

[0178] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage of the nitrile additive in the electrolyte is adjusted to 0.5%, and the mass percentage of the ether nitrile additive in the electrolyte is adjusted to 1%.

[0179] Embodiment 24

[0180] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage of the nitrile additive in the electrolyte is adjusted to 13%.

[0182] Embodiment 25

[0183] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage of the ether nitrile additive in the electrolyte is adjusted to 10%.

[0184] Embodiment 26

[0185] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass percentage content of the nitrile additive in the electrolyte is adjusted to 0.1%.

[0186] Embodiment 27

[0187] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the formation pressure is 1.1 MPa.

[0188] Embodiment 28

[0189] The method for making the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass content of the ternary positive electrode material NCM613 in the fourth positive electrode active layer is set to 50% in the positive electrode active material; substituting into y=p*ln(m)+q, it is calculated that p=-0.361, q=1, then y=-0.361*ln(m)+1; then the mass content of the ternary positive electrode material in the second positive electrode active layer is 74.98% in the positive electrode active material, and the mass content of the ternary positive electrode material in the third positive electrode active layer is 60.34% in the positive electrode active material;

[0190] Then the mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the second positive electrode active layer slurry is 72.35:24.15:2:1.5;

[0191] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the third positive electrode active layer slurry is 58.23:38.27:2:1.5.

[0192] Embodiment 29

[0193] The manufacturing method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass content of the ternary positive electrode material NCM613 in the first positive electrode active layer is 90% in the positive electrode active material; substituting into y=p*ln(m)+q, it is calculated that p=-0.649, q=0.9, then y=-0.649*ln(m)+0.9; then the mass content of the ternary positive electrode material in the second positive electrode active layer is 45.01% in the positive electrode active material, and the mass content of the ternary positive electrode material in the third positive electrode active layer is 18.70% in the positive electrode active material;

[0194] Then the mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the second positive electrode active layer slurry is 43.44:53.06:2:1.5;

[0195] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the third positive electrode active layer slurry is 18.05:78.45:2:1.5.

[0196] Comparative Example 1

[0197] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that, in step 1), the first layer of positive electrode active layer slurry, the second layer of positive electrode active layer slurry, the third layer of positive electrode active layer slurry and the fourth layer of positive electrode active layer slurry are mixed uniformly to obtain positive electrode slurry, and the positive electrode slurry is applied to the surface of aluminum foil, and the positive electrode sheet is obtained after drying, rolling and slitting, and the thickness of the positive electrode active layer is 222.32 μm. The rest is consistent with Example 1.

[0198] Comparative Example 2

[0199] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass content of the ternary positive electrode material in the first positive electrode active layer is 0, the mass content of the ternary positive electrode material in the second positive electrode active layer is 20.8%, the mass content of the ternary positive electrode material in the third positive electrode active layer is 50%, and the mass content of the ternary positive electrode material in the fourth positive electrode active layer is 100%;

[0200] Then the mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the first positive electrode active layer slurry is 0:96.5:2:1.5;

[0201] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the second positive electrode active layer slurry is 20.06:76.44:2:1.5;

[0202] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the third positive electrode active layer slurry is 48.27:48.23:2:1.5;

[0203] The mass ratio of the ternary positive electrode material, lithium iron phosphate, conductive agent and binder in the slurry of the fourth positive electrode active layer is 96.5:0:2:1.5.

[0204] Comparative Example 3

[0205] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that, in step 1), there are two positive electrode active layers, the mass content of the ternary positive electrode material in the positive electrode active material in the first positive electrode active layer is 100%, and the mass content of lithium iron phosphate in the positive electrode active material is 0, and the mass content of the ternary positive electrode material in the second positive electrode active layer is 0, and the mass content of lithium iron phosphate in the positive electrode active material is 100%;

[0206] The thickness of the first positive electrode active layer and the second positive electrode active layer were both set to 100 μm.

[0207] Test example

[0208] 1. The energy density, cycle performance, fast charging performance, furnace temperature safety performance and lithium precipitation phenomenon of the lithium ion batteries prepared in the above embodiments and comparative examples were tested. The test results are shown in Table 1.

[0209] 1) Cycle performance

[0210] At an ambient temperature of 25°C, the battery was charged to 3.5V at 2C with a cutoff current of 1C, then charged to 3.65V at 1C with a cutoff current of 0.05C, and then discharged to 2.5V at 0.5C, with the discharge capacity recorded as C0. The battery was cycled according to the above-mentioned charge and discharge mechanism for 600 cycles, and the discharge capacities at 300 and 600 cycles were recorded as C1 and C2, respectively. The capacity retention rate after 300 cycles (%) = C1 / C0×100%, and the capacity retention rate after 600 cycles (%) = C2 / C0×100%. The test results are shown in Table 1.

[0211] The lithium-ion batteries that have been cycled to 300 and 600 cycles were disassembled to observe whether there were black spots on the anode interface, and the results were recorded.

[0212] 2) Battery rate performance

[0213] The rate performance of the battery is determined by charging the battery at a rate of 25°C. The details are as follows:

[0214] At 25°C, the battery state voltage, internal resistance, and thickness were tested, and the battery was left standing for 10 minutes; the battery was discharged at 0.2C to 3.0V and left standing for 10 minutes; the battery was charged at 0.2C, 0.3C, and 0.4C to the upper limit voltage (4.45V in the present invention), with a cut-off current of 0.05C, and left standing for 10 minutes; the battery was discharged at 0.5C to 3.0V and left standing for 10 minutes. After 30 cycles according to the above charging and discharging mechanism, the battery was fully charged and disassembled.

[0215] Observe the anode interface. If the anode electrode is golden and normal, and there is no lithium deposition, the battery supports the corresponding rate performance. If there are gray / brown / white particles covering the interface, the battery is lithium deposition, and the corresponding rate performance is not supported at this time. The maximum rate at which the battery does not deposit lithium is the rate performance of the battery.

[0216] 3) Furnace temperature safety performance

[0217] For each example and comparative example, 5 lithium-ion batteries were taken as a group. At an ambient temperature of 25°C, they were discharged at 0.2C to a cut-off voltage of 3.0V and left to stand for 5 minutes. Then they were charged at a constant current and constant voltage of 0.5C to an upper limit voltage of 4.45V and a cut-off current of 0.05C. At this time, the battery was fully charged and photographed. Then, the fully charged battery was placed in a test box and heated at 5°C / min. When the temperature in the box reached 140°C±2°C, the temperature was kept constant for 60 minutes. After the test, photographs were taken. If the battery did not catch fire or explode, it was considered to have passed. The number of batteries that passed in each group was recorded. The test results are shown in Table 1.

[0218] Table 1

[0219]

[0220]

[0221] From Table 1, we can see that:

[0222] Compared with Comparative Examples 1 to 3, the lithium-ion batteries in Examples 1 to 29 have higher cycle performance, fast charging performance and furnace temperature safety performance, and the lithium plating problem during the cycle is effectively improved. Among them, the capacity retention rate of the lithium-ion battery in Example 10 can reach 95.45% after 300 cycles, and the capacity retention rate is still 90.51% when it is cycled to 600 cycles, and there is no lithium plating in the pole pieces; in addition, it can also pass the furnace temperature safety performance test. It can be seen that the positive electrode sheet in the present invention can make the lithium-ion battery have both high energy density and safety performance.

[0223] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and n positive electrode active layers disposed on at least a portion of the surface of the positive electrode current collector, where n is an integer greater than or equal to 3; The n positive electrode active layers are stacked in sequence on a surface perpendicular to the positive electrode current collector, each positive electrode active layer comprises a positive electrode active material, and the positive electrode active material comprises lithium iron phosphate and a ternary positive electrode material; In the thickness direction of the positive electrode active layer, from the side close to the positive electrode collector surface to the side away from the positive electrode collector surface, the mass content of the ternary positive electrode material in each layer of the positive electrode active layer gradually decreases, and the mass content of lithium iron phosphate in each layer of the positive electrode active layer gradually increases.

2. The positive electrode sheet according to claim 1, characterized in that: In the positive electrode active material of the first positive electrode active layer, the mass content of the ternary positive electrode material is not less than 99%; And / or, in the positive electrode active material of the n-th positive electrode active layer, the mass content of the lithium iron phosphate is not less than 99%.

3. The positive electrode sheet according to claim 2, characterized in that: The thickness of the first positive electrode active layer is equal to the thickness of the nth positive electrode active layer; Preferably, the total thickness H of the n-layer positive electrode active layer on one side is ≤400 μm.

4. The positive electrode sheet according to claim 3, characterized in that: The outer surface of the positive electrode active layer is provided with a recessed portion; Preferably, the depth d of the recessed portion is equal to the single-side thickness h of the nth positive electrode active layer. n Satisfied: 0.01h n ≤d≤h n ; More preferably, the depth d of the recessed portion is 1 to 20 μm.

5. The positive electrode sheet according to claim 4, characterized in that: The maximum size s of the recessed portions is 5 to 200 μm, and / or the interval t of the recessed portions is 100 to 2000 μm.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The median particle size Dv50 of the ternary positive electrode material is 5 to 15 μm, and / or the median particle size Dv50 of the lithium iron phosphate is 1 to 2.5 μm.

7. A lithium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 6.

8. The lithium-ion battery according to claim 7, characterized in that: The lithium-ion battery further comprises an electrolyte, wherein the electrolyte comprises a nitrile additive and an ether nitrile additive; The nitrile additive includes at least one of succinonitrile, 1,3,6-hexanetricarbonitrile, 1,3,5-pentanetricarbonitrile, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, tricyanobenzene, acrylonitrile, and 1,2,3-tris(cyanoethoxy)propane; The ether nitrile additive includes at least one of 1,2,3-tri(cyanoethoxy)propane, ethylene glycol di(2-cyanoethyl) ether, and diethylene glycol di(2-cyanoethyl) ether.

9. The lithium-ion battery according to claim 8, characterized in that: The sum of the mass percentage content i of the nitrile additive and the mass percentage content j of the ether nitrile additive in the electrolyte is 2 to 18%; Preferably, 2i≤j; More preferably, i is 0.1 to 10%, and / or j is 0.1 to 8%.

10. The lithium ion battery according to claim 9, characterized in that: The lithium-ion battery meets the following requirements: 0.5h n / H≤i≤5h n / H+8,0.5h n / H≤j≤5h n / H+8.

Citation Information

Patent Citations

  • Preparation method of power lithium ion battery

    CN112186259A

  • High-safety positive plate and lithium ion battery thereof

    CN112467107A

  • Lithium ion battery

    CN114497468A

  • Positive plate, preparation method thereof and battery

    CN116885097A